2020
DOI: 10.1016/j.annemergmed.2020.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Immediate Versus Early Antibiotics in Severe Sepsis and Septic Shock: A Systematic Review and Meta-analysis

Abstract: Study objective: Debate exists about the mortality benefit of administering antibiotics within either 1 or 3 hours of sepsis onset. We performed this meta-analysis to analyze the effect of immediate (0 to 1 hour after onset) versus early (1 to 3 hours after onset) antibiotics on mortality in patients with severe sepsis or septic shock.Methods: This review was consistent with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Searched databases included PubMed, EMBASE, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 59 publications
2
30
1
2
Order By: Relevance
“…Besides, the relatively lower baseline blood pressure in cirrhotic patients made the decision of early support of vasopressors for their hypotension more challenging [4]. In addition, the survival benefit of early administration of antimicrobial agents in septic shock patients has been questioned in several meta-analysis studies [28,29]. Taken together, little evidence exists to support that each component of the hour-1 bundle is equally effective and can be applied with equal consistency, especially in a physiologically unique and fragile cirrhosis group [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the relatively lower baseline blood pressure in cirrhotic patients made the decision of early support of vasopressors for their hypotension more challenging [4]. In addition, the survival benefit of early administration of antimicrobial agents in septic shock patients has been questioned in several meta-analysis studies [28,29]. Taken together, little evidence exists to support that each component of the hour-1 bundle is equally effective and can be applied with equal consistency, especially in a physiologically unique and fragile cirrhosis group [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…51 Likewise, a metaregression analysis of 13 studies concluded that there was no difference in mortality between patients receiving antibiotics within one or three hours after the onset of sepsis. 52 In contrast, in a meta-analysis of 10 studies Johnston et al found a 33% reduction in the odds of mortality among patients in whom antibiotics were administred within one hour. 53 Yet, their findings were largely influenced by one study that reported a 7.5% linear increase in the risk of mortality after adjusting for numerous covariables including geographic locations.…”
Section: Fig 2 Study Enrolment Periodsmentioning
confidence: 94%
“…Our group recently published a meta-analysis comparing severe sepsis/septic shock mortality in those who received antibiotics at < 1 h vs 1 to 3 h after arrival/onset. 2 We found no mortality difference between these two early times although antibiotic appropriateness was not our focus.…”
Section: Mortality Benefit Inconclusive Based On This Reviewmentioning
confidence: 61%
“…This biases toward no effect of delayed therapy. 2 We avoided this by studying appropriate or active antibiotic therapy. 3 Most studies included in our analysis defined delayed therapy as > 24 h because (1) delays this long are common (> 30% in the United States) 4 ; and (2) data from mixed septic/nonseptic populations suggest 24 to 48 h is the time threshold at which mortality increases the most.…”
Section: Responsementioning
confidence: 99%